2003
DOI: 10.1074/jbc.m209911200
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Donors Inhibit Luciferase Expression in a Promoter-independent Fashion

Abstract: Nitric oxide (NO) is an important molecule with diverse bio-messenger functions including regulation of gene expression. Transcriptional studies using sensitive luciferase reporter systems have suggested that NO inhibits the promoter activity of a variety of genes. Here we report that NO donors (sodium nitroprusside, 2,2-(hydroxynitrosohydrazono)bis-ethanimine, and (؎)-(E)-4-ethyl-2-[(Z)-hydroxyimino]-5-nitro-3-hexen-1-yl-nicotinamide) decrease luciferase activity in a promoterindependent fashion in both viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…This showed that expression of F-LARP4 stabilized luciferase mRNA compared to the vector control, in which luciferase mRNA decayed with a half-life of ϳ4 h (Fig. 9A, vector), in agreement with previous reports (4,23). We conclude that enhanced expression of LARP4 prolonged luciferase mRNA half-life.…”
Section: Vol 31 2011supporting
confidence: 80%
See 1 more Smart Citation
“…This showed that expression of F-LARP4 stabilized luciferase mRNA compared to the vector control, in which luciferase mRNA decayed with a half-life of ϳ4 h (Fig. 9A, vector), in agreement with previous reports (4,23). We conclude that enhanced expression of LARP4 prolonged luciferase mRNA half-life.…”
Section: Vol 31 2011supporting
confidence: 80%
“…ITC of PAM2w-MLLE interactions was carried out in 50 mM NaH 2 PO 4 , 100 mM NaCl, pH 7.0, with a protein concentration of 170 M for 4.5 mM LARP4 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) peptide and a protein concentration 85 M for 1.6 mM LARP4 .…”
Section: Cloning Hela Poly(a)mentioning
confidence: 99%
“…The pGL3 control vector expressing the luciferase under the control of the SV40 promoter was highly expressed in these cells and there was a 60 % reduction in luciferase activity following DETA/NO treatment (results not shown), as previously reported [37]. Transient transfections of HuH7 cells with the pGL2-IRP1P0.1 construct containing the minimal promoter fragment showed that the basal luciferase activity produced by this construct was very low and treatment of the cells for 48 h with a chemical NO donor (DETA/NO, 250 µM), induced a statistically significant 2-fold reduction (P < 0.05) in luciferase activity ( Figure 1C).…”
Section: Predominant Role Of the Gas Sequence In The Inhibition Of Mosupporting
confidence: 66%
“…The mild inhibitory effect of NaN 3 or rotenone on ChoRE-mutated Txnip promoter might be due to residual activities of the mutated ChoREs or, more likely, was not Txnip promoter-specific. For instance, the OXPHOS inhibitor NO has been shown to repress the luciferase expression in a promoter-independent fashion (28). Thus, we conclude that OXPHOS inhibitors repress the Txnip expression at the transcriptional level, which is mediated largely by the ChoREs on the Txnip promoter.…”
Section: Chores Mediate the Effect Of Oxphos Inhibitors On Thementioning
confidence: 79%